Adsorption of Heavy Metals by Bio-Chars Produced from Pyrolysis of Paper Mulberry from Simulated Industrial Wastewater - Adil, S.; Mashiatullah, A.; Asma, M.; Ghaffar, A.; Khan, S.; Abid, J. (The Nucleus, 2014)
Paper mulberry bio-char (by-product of pyrolysis) was evaluated for the removal of heavy metals (Cd, Cr, Cu, Zn and Pb) from simulated industrial waste water. The surface properties and surface area of the bio-char was found suitable for metal adsorption. Batch sorption studies for adsorption potential of paper mulberry bio-char for Cd, Cr, Cu, Pb and Zn were investigated under different experimental conditions of pH, temperature and contact time. Maximum removal efficiency of Cd, Cu, Pb and Zn was 97.8, 76.8, 85.6, and 82.2 % respectively at pH 12 while maximum removal of Cr was recorded (98%) at pH 2. The removal efficiency showed different behaviour at different contact times. Maximum removal efficiency of Cd, Cr, Zn was 81, 86, 61.4% at contact time of 3 hr. The maximum removal of Cu was 64.2% observed at a contact time of 4 hours while the maximum removal of Pb and Zn was 85% at contact time of 2 hr. The values of the thermodynamic parameters, enthalpy ∆Ho , Gibbs free energy ∆G° of sorption and entropy ∆So were calculated to define endothermic or exothermic behavior of the sorbent used. Negative value of ∆G° for Cd, Cu, Cr and Pb indicated paper mulberry bio-char as a feasible sorbent for the efficient removal of Cd, Cu, Cr and Pb. Negative value of ∆H◦ was observed for Cd and Pb indicating that the adsorption process is exothermic while positive value of ∆H◦ was calculated for Cu, Cr and Zn showed that the adsorption is endothermic. The results obtained showed that plant residue bio-char can act as an effective sorbent for the removal of heavy metals from aqueous solutions.